Effective risk management practice in Somalia Islamic banks - Barre, Galad Mohamed (Asian Economic and Financial Review, 2024)
This paper aims to assess the degree to which Somali banks use effective risk management practices (RMPs). Furthermore, the study has explored the level of risk management practices using the original components of risk management aspects, including understanding risk and risk management, risk assessment and analysis, risk identification, risk monitoring, and credit risk analysis, with the addition of perceived trust to the original constructs of risk management aspects. The study is based on a questionnaire survey of 423 banking staff from 13 licensed banks in Somalia. The researcher adopted a questionnaire that covers six aspects of risk management with perceived trust: understanding risk and risk management, risk assessment and analysis, risk identification, risk monitoring, credit risk analysis, perceived trust, and RMPs. This study found that the staff of Somalia have a clear understanding of risk and risk management and have efficient risk identification, risk assessment, risk monitoring, credit risk analysis, perceived trust, and risk management practices. In addition, the respondents also recognize that the banks do not have deposit insurance, which is a risk to the depositors if the bank goes bankrupt. The paper’s findings are limited to the risk management aspects of the bank industry, with additional perceived trust in Somalia. The paper explores the risk management practice in the Somali bank sector. The results can be used as valuable feedback for improving risk management practice in the banking industry. This study is the first research attempt to investigate risk management practice with additional trust.